(3eNJUQ ebGdI LGdjfhS aj GdMK Ydi JYde GdYdhe hGdUfGYGJs
(3ChdgG (B:s
(3bGd CeG GdCeQ ai GdMjhGf GdPi jSei ZjQ fGWb dG fWb dg GdHJg aZjQ eJHjf dCfg bO jchf hEf cGf djS dg GdfWb GddaXi s
(3BNQgG (B:s
(3hYGQkG Ydjg EPG cGf bO YLR Yf GdTF GdfGbU hEf fGdg def JaVd GdHgGFe JeJ hGdeLO hGdTcQ ddg OGFekG CHOkG TQeOkG JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs